PRIVATISASI BUMN PERSERO - AMINUDDIN, - (1999)
This research is based on the theoritical and. practical debate concerning privatization in Indonesia. Privatization isa process or manner in which the ownership and the operation of state property is transferred to the private sector. Some basic problems worth examine are {1) How is the base framework and direction privatization of BUMN particularly which are related with the meaning privatization, purpose and pri-vatization process, legal statue of BUMN resulting in the change of the BUMN legal· arrangement {2) How is the privatization of BUMN is not against the provision of article 33 (2) of · the 1945 constitution {3) How is the criteria being used in the privatization of BUMN in Indonesia concerning the branches of production clasified as important to the country which dominate the lives of most of the people. From the research it is evident that privatization of BUMN in Indonesia dealing with the legal statue of BUMN and resulted in the change of the legal arrangement towards a BUMN would have a legal affect in the competence of regulating and developing BUMN which is no longer executed directly to each BUMN, but rather has to follow a mechanism through a RUPS based according law No. 1/1995 concerning PT. Implication of privatization BUMN which related article 33 (2) of the 1945 constitution is a competence owned by the state to regulate the allotment and development of the branches of production important to the state and dominate the lives of most the people. The domination of the state does not really means the owner in which the operation could be hand over to other party. On the contrary, the meaning of state domination is construed as a state competence to regulate the allotment and the development which resulted the operation of the branches of production could be transfered some part to the other party through KSP or KSO. It could be concluded that the privatization of BUMN is not incompatible with the provision of article 33 (2) of the 1945 constitution as . far as the state competence is concerned. On the other hand, one basic criteria in conducting privatization of BUMN is that in the case of a BUMN which operate the branches of production important to the state and dominate the lives of the people, then the privatization should not be carried out totally in full in order to keep the existance of the state competence. On the contrary, a BUMN which operate branches of production and considered not eo important to the state and does not dominate the lives of the people, in this case the privatization can be conducted in full, thoroughly.